Secondary battery, preparation method thereof and power utilization device

By adding an alloy layer on the surface of the current collecting layer of the electrode sheet of the lithium-ion battery and setting an electrode film layer on the basis of the alloy layer, the problem of adhesive floating is solved, the energy density and capacity retention rate of the battery are improved, and the safety performance is enhanced.

CN119852483APending Publication Date: 2025-04-18CATL (JIANGSU) NEW ENERGY TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411010750.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The electrode sheets of the existing lithium-ion batteries are prone to problems of adhesive floating during the coating process, resulting in a reduction in the transmission channels of lithium ions and affecting the battery's capacity retention rate and safety performance.

Method used

By adding an alloy layer on the surface of the current collecting layer and installing an electrode film layer on the basis of the alloy layer, the alloy layer has good conductivity, hardness and toughness, reducing or not using adhesive, and improving the bonding strength between the electrode film layer and the current collecting layer.

Benefits of technology

The amount of binder added is reduced, the amount of active material added is increased, the energy density and capacity retention rate of the battery are enhanced, and the safety performance of the electrode sheet is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852483A_ABST
    Figure CN119852483A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery, a preparation method thereof and a power utilization device, and relates to the technical field of batteries. The secondary battery comprises an electrode plate, wherein the electrode plate comprises a current collector layer and an electrode film layer attached to the surface of the current collector layer; the current collector layer comprises a current collecting layer and an alloy layer which are stacked, and the alloy layer is close to the electrode film layer; the electrode film layer comprises an active material and a binder, and the content of the binder is 0-0.4 wt% based on the total mass of the electrode film layer. According to the secondary battery, the battery pack and the power utilization device, the problem of powder falling can be reduced on the basis of reducing or not using a binder, so that the addition amount of the active material is increased, and the energy density of the secondary battery is improved; besides, the content of the binder is reduced, and the problem that the binder floats upwards in the electrode plate can be improved, so that more active ion transmission channels can be provided, and the capacity retention ratio of the secondary battery is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electrical device, as well as a method for preparing an electrode plate. Background Art

[0002] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.

[0003] At present, the electrode plates of lithium-ion batteries are formed by coating. In the coating process, a slurry with good stability, good viscosity and good fluidity is evenly coated on the current collector. Such electrode plates usually contain a certain amount of binder. During the drying process after the slurry is coated, the binder will float up, resulting in a reduction in the transmission channel of lithium ions, thereby reducing the capacity retention rate of the battery. Summary of the invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a secondary battery and its preparation method and electrical device, which can reduce the powder loss problem on the basis of reducing or not using a binder, thereby increasing the amount of active material added to improve the energy density of the secondary battery; in addition, the reduction of the binder content can improve the problem of binder floating in the electrode plate, thereby providing more active ion transmission channels to increase the capacity retention rate of the secondary battery.

[0005] The first aspect of the present application provides a secondary battery, which includes an electrode plate, the electrode plate includes a current collector layer and an electrode film layer attached to the surface of the current collector layer; the current collector layer includes a current collector layer and an alloy layer arranged in a stacked manner, and the alloy layer is close to the electrode film layer; the electrode film layer includes an active material and a binder, and the content of the binder is 0 to 0.4 wt% based on the total mass of the electrode film layer.

[0006] In order to increase the bonding ability between the current collector layer and the electrode film layer of the secondary battery, a certain amount of binder (for example: 1wt%~3wt%) is usually added to the electrode film layer. Due to the large amount of binder added, the binder is prone to floating, resulting in the formation of a polymer film layer including the binder on the surface of the electrode film layer, affecting the transmission of active ions. The floating of the binder will reduce the transmission channels of the active ions, thereby reducing the capacity retention rate of the secondary battery. The secondary battery provided by the present application adds an alloy layer on the surface of the current collecting layer, and arranges an electrode film layer on the basis of the alloy layer. The alloy layer has good conductivity, high hardness and toughness, and a certain ability to resist chemical corrosion. The current collecting layer can be modified by the alloy layer, the internal resistance of the secondary battery can be reduced, and the bonding strength between the electrode film layer and the current collecting layer can be improved, thereby reducing the powder falling problem on the basis of reducing or not using the binder in the electrode film layer. The amount of binder added is very little or even no, thereby increasing the amount of active material added to improve the energy density of the secondary battery; in addition, the reduction in binder content can improve the problem of binder floating in the electrode pole piece, thereby providing more active ion transmission channels to increase the capacity retention rate of the secondary battery.

[0007] In any embodiment, the electrode plate includes a negative electrode plate, and the tensile strength of the negative electrode plate is 400Mpa to 900Mpa. The tensile strength of the negative electrode plate is high. During the charge and discharge process, even if the secondary battery has a small amount of expansion, the expansion problem can be improved due to the high strength of the negative electrode plate, thereby improving the capacity retention rate of the secondary battery. In addition, for the negative electrode plate, improving the active ion transmission channel can effectively improve the lithium precipitation problem, thereby improving the capacity retention rate and safety performance of the secondary battery.

[0008] In any embodiment, the electrode plate includes a positive electrode plate, and the tensile strength of the positive electrode plate is 200Mpa to 400Mpa. The tensile strength of the positive electrode plate is relatively high. During the charge and discharge process, even if the secondary battery has a small amount of expansion, the expansion problem can be improved due to the high strength of the positive electrode plate, thereby improving the capacity retention rate of the secondary battery.

[0009] In any embodiment, the surface roughness Ra of the alloy layer is 15nm to 50nm. When the surface roughness of the alloy layer is within the above range, the bonding strength between the electrode film layer and the current collector layer can be further improved, and the amount of binder added can be further reduced to further improve the energy density and capacity retention rate of the secondary battery.

[0010] In any embodiment, the electrode plate includes a negative electrode plate, and the adhesion between the current collector layer and the electrode film layer in the negative electrode plate is 12N / m to 25N / m. The negative electrode current collector contains an alloy layer, which can make the adhesion between the negative electrode current collector and the negative electrode film layer of the negative electrode plate within the above range, so that in the case of a small amount of binder or no binder, the bonding force between the negative electrode current collector and the negative electrode film layer is basically not affected, so as to reduce the problem of powder falling. In addition, for the negative electrode plate, a small amount of binder is added or no binder is added, which can improve the active ion transmission channel, can effectively improve the lithium precipitation problem, thereby improving the capacity retention rate and safety performance of the secondary battery.

[0011] In any embodiment, the electrode plate includes a positive electrode plate, and in the positive electrode plate, the bonding force between the current collector layer and the electrode film layer is 15N / m to 50N / m. The positive electrode current collector contains an alloy layer, so that the bonding force between the positive electrode current collector and the positive electrode film layer of the positive electrode plate is within the above range, so that in the case of a small amount of binder or no binder, the bonding force between the positive electrode current collector and the positive electrode film layer is basically not affected, so as to reduce the problem of powder falling.

[0012] In any embodiment, the electrode sheet includes a negative electrode sheet, and the surface density of the negative electrode sheet is 300 mg / cm 2 ~400mg / cm 2 The negative electrode current collector contains an alloy layer, which can improve the compactness of the negative electrode film layer on the alloy layer, so that the surface density of the negative electrode sheet is within the above range, thereby improving the energy density of the secondary battery.

[0013] In any embodiment, the electrode sheet includes a positive electrode sheet, and the surface density of the positive electrode sheet is 500 mg / cm 2 ~1000mg / cm 2 The positive electrode current collector contains an alloy layer, which can improve the compactness of the positive electrode film layer on the alloy layer, so that the surface density of the positive electrode sheet is within the above range, thereby improving the energy density of the secondary battery.

[0014] In any embodiment, the alloy layer contains at least four metal elements, including Co and Ni. The alloy layer contains at least four metal elements, which is a mixture of multiple metals, has a high entropy effect, and can make the alloy layer have the comprehensive properties of high conductivity, high strength, high toughness and chemical corrosion resistance; in addition, it contains Co and Ni elements, which as a current collector layer structure, has more stable electrochemical performance and basically does not undergo chemical reactions during the charge and discharge process.

[0015] In any embodiment, the electrode plate includes a negative electrode plate, and in the negative electrode plate, the alloy layer includes, based on the total mass of the alloy layer: Fe: 23wt% to 40wt%, Co: 10wt% to 30wt%, Ni: 20wt% to 35wt%, Cu: 15wt% to 35wt%, C: 7wt% to 15wt%. The composition of the alloy layer of the negative electrode collector layer is within the above range, which can make the tensile strength of the negative electrode plate higher.

[0016] In any embodiment, the electrode plate includes a positive electrode plate, in which the alloy layer includes, based on the total mass of the alloy layer: Al: 17wt% to 29wt%, Fe: 16wt% to 29wt%, Co: 16wt% to 20wt%, Ni: 14wt% to 20wt%, Li: 15wt% to 21wt%. The composition of the alloy layer of the positive current collector layer is within the above range, which can make the tensile strength of the positive electrode plate higher.

[0017] In any embodiment, the thickness of the current collector layer is 4 μm to 15 μm; and / or, the thickness of the alloy layer is 10 nm to 50 nm; and / or, the thickness of the electrode film layer is 25 μm to 100 μm. By using a current collector layer of a certain thickness and an alloy layer of a certain thickness, the modification effect of the current collector layer is better, so that the conductivity of the current collector layer is better, and the internal resistance of the secondary battery can be further reduced; in addition, an electrode film layer of a certain thickness can be formed on the current collector layer, and the electrode film layer has good adhesion and is not easy to fall off.

[0018] In any embodiment, the electrode film layer further includes a conductive agent and a dispersant. Based on the total mass of the electrode film layer, the electrode film layer includes: 96wt% to 99wt% active material, 0.2wt% to 2.8wt% conductive agent, 0 to 1.5wt% dispersant, and 0 to 0.4wt% binder. By increasing and reducing the amount of binder and increasing the content of active material, the energy density of the secondary battery can be increased.

[0019] The second aspect of the present application also provides a method for preparing a secondary battery, comprising: forming an electrode film layer on the surface of a current collector layer by plasma spraying to obtain an electrode plate; wherein the current collector layer comprises a current collector layer and an alloy layer arranged in a stacked manner, the alloy layer is close to the electrode film layer, the electrode film layer comprises an active material and a binder, and the content of the binder is 0 to 0.4 wt % based on the total mass of the electrode film layer. The electrode plate is combined with a separator to form a secondary battery.

[0020] An alloy layer is added to the surface of the current collecting layer. The alloy layer has good conductivity, high hardness and toughness, and a certain resistance to chemical corrosion. By modifying the current collecting layer with the alloy layer, the internal resistance of the secondary battery can be reduced. In addition, due to the high strength and toughness of the alloy layer, an electrode film layer can be formed by plasma spraying. The plasma spraying method melts the surface of the active material and forms it on the current collecting layer, which can increase the density of the electrode film layer and improve the bonding ability between the electrode film layer and the current collecting layer. The content of the binder can be reduced to form an electrode film layer with less or even no binder, and the bonding strength between the electrode film layer and the current collecting layer can still meet the demand, thereby increasing the amount of active material added to improve the energy density of the secondary battery. In addition, the reduction in the binder content can improve the problem of binder floating in the electrode pole piece, thereby providing more active ion transmission channels to increase the capacity retention rate of the secondary battery.

[0021] In any embodiment, the electrode plate is a negative electrode plate, and the conditions for plasma spraying include: the active material of the negative electrode plate includes a carbon material, and the temperature of plasma spraying is 1000° C. to 3000° C. Spraying the negative electrode active material within the spraying temperature range can make the surface of the carbon material form a molten state, so that it is formed on the surface of the negative electrode current collector layer, and the bonding strength between the negative electrode current collector layer and the negative electrode film layer is high.

[0022] In any embodiment, the electrode plate is a negative electrode plate, and the plasma spraying conditions include: the spraying rate of the plasma spraying is 100 g / min to 200 g / min. The spraying rate is selected within this range, so that the thickness uniformity of the negative electrode film layer formed on the negative electrode current collector layer can be better.

[0023] In any embodiment, the electrode plate is a negative electrode plate, and the conditions for plasma spraying include: along the thickness direction of the electrode film layer, the distance between the plasma spraying nozzle and the surface of the electrode film layer is 100 mm to 250 mm. The distance is limited within this range, and the time range for the active material to come out from the nozzle to the current collector layer can be controlled laterally to adjust the state of the molten active material during the spraying process, so as to make the particles of the active material more uniformly dispersed, so that the active material of the negative film layer formed on the negative current collector layer is more uniformly dispersed, the problem of particle adhesion can be improved, and the bonding ability between the negative current collector layer and the negative film layer can be improved.

[0024] In any embodiment, the electrode plate is a negative electrode plate, and the conditions for plasma spraying include: the spray angle between the spraying direction of the plasma spraying and the thickness direction of the electrode film layer is 55° to 85°. This can not only make the uniformity of the negative electrode film layer better, but also make the dispersion of the negative electrode active material more uniform, so as to form a negative electrode film layer with better density and uniformity, so as to improve the surface density of the negative electrode plate, and at the same time improve the bonding ability between the negative electrode current collector and the negative electrode film layer.

[0025] In any embodiment, the electrode plate is a positive electrode plate, and the conditions for plasma spraying include: the temperature of plasma spraying is 800° C. to 1500° C. Spraying the positive electrode active material within the spraying temperature range can make the surface of the positive electrode active material form a molten state, so that it is formed on the surface of the positive electrode current collector layer, and the bonding strength between the positive electrode current collector layer and the positive electrode film layer is high.

[0026] In any embodiment, the electrode plate is a positive electrode plate, and the plasma spraying conditions include: the spraying rate of the plasma spraying is 100 g / min to 200 g / min. The spraying rate is selected within this range, so that the thickness uniformity of the positive electrode film layer formed on the positive electrode current collector layer can be better.

[0027] In any embodiment, the electrode plate is a positive electrode plate, and the conditions for plasma spraying include: along the thickness direction of the electrode film layer, the distance between the plasma spraying nozzle and the surface of the electrode film layer is 100mm to 250mm. The distance is limited within this range, and the time range for the active material to come out from the nozzle to the current collector layer can be controlled laterally to adjust the state of the molten active material during the spraying process, so as to make the particles of the active material more uniformly dispersed, so that the active material of the positive film layer formed on the positive current collector layer is more uniformly dispersed, the problem of particle adhesion can be improved, and the bonding ability between the positive current collector layer and the positive film layer can be improved.

[0028] In any embodiment, the electrode plate is a positive electrode plate, and the conditions for plasma spraying include: the spray angle between the spraying direction of the plasma spraying and the thickness direction of the electrode film layer is 55° to 85°. This can make the uniformity of the positive electrode film layer better, and also make the dispersion of the positive electrode active material more uniform, so as to form a positive electrode film layer with better density and uniformity, so as to improve the surface density of the positive electrode plate, and at the same time improve the bonding ability between the positive current collector layer and the positive electrode film layer.

[0029] In any embodiment, magnetron sputtering is used to form an alloy layer on the surface of the current collector layer. The alloy layer can be formed by the magnetron sputtering method, and a relatively uniform alloy layer can be obtained to further improve the conductivity and strength of the alloy layer. The third aspect of the present application provides an electrical device, including the secondary battery of the first aspect of the present application, or the electrode pole piece prepared according to the preparation method of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of an electrode plate according to one embodiment of the present application.

[0031] Figure 2 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0032] Figure 3 yes Figure 2 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0033] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.

[0034] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0035] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0036] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0037] Figure 8 This is a cross-sectional scanning electron microscope image of the negative electrode plate provided in Example 1-1 of the present application.

[0038] Fig. 9 This is a cross-sectional scanning electron microscope image of the negative electrode sheet provided in Comparative Example 1 of the present application.

[0039] Description of reference numerals:

[0040] 10 current collector layer; 11 current collector layer; 12 alloy layer; 20 electrode film layer; 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0041] Below, the secondary battery, the electrical device, and the method for preparing the electrode plate of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0042] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0043] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0044] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0045] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0046] At present, the positive and negative electrodes of lithium-ion batteries are formed by coating (such as extrusion coating). In the coating process, the slurry with good stability, good viscosity and good fluidity is evenly coated on the positive and negative current collector layers. This coating method requires the addition of some binders in the slurry, and the binder content is usually 1wt% to 3wt% to achieve the purpose of bonding between active materials and good bonding with the current collector layer. However, the binder itself is a process additive, which essentially cannot improve the performance of the battery. On the contrary, due to the large amount of binder added, the binder will float up, so that a polymer film layer including the binder is formed on the surface of the electrode film layer, affecting the transmission of active ions. For the positive electrode, the binder floats up and reduces the lithium ion transmission channel, thereby affecting the capacity retention rate of the secondary battery; for the negative electrode, the binder floats up and reduces the lithium ion transmission channel, thereby reducing the lithium insertion site, causing the problem of lithium precipitation on the surface of the negative electrode, which will reduce the capacity retention rate of the secondary battery, and even cause lithium dendrites, resulting in the rupture of the isolation film, affecting the safety performance of the secondary battery.

[0047] Based on this, a first aspect of the embodiments of the present application provides a secondary battery, the secondary battery comprising an electrode plate, Figure 1 The electrode sheet structure is taken as an example, including a current collector layer 10 and an electrode film layer 20 attached to the surface of the current collector layer 10, the current collector layer 10 includes a current collector layer 11 and an alloy layer 12 which are stacked, and the alloy layer 12 is close to the electrode film layer 20; the electrode film layer 20 includes an active material and a binder, and the content of the binder is 0 to 0.4 wt% based on the total mass of the electrode film layer.

[0048] In the embodiment of the present application, the structure of the electrode plate can be: an alloy layer 12 and an electrode film layer 20 are sequentially arranged on one surface of the current collecting layer 11, and the current collecting layer 10 is composed of the current collecting layer 11 and an alloy layer 12. The structure of the electrode plate can also be: an alloy layer 12 and an electrode film layer 20 are sequentially arranged on two surfaces of the current collecting layer 11, and the current collecting layer 10 is composed of the current collecting layer 11 and two alloy layers 12.

[0049] Reference Figure 1According to the embodiment in which the electrode film layer 20 is disposed on one side surface of the current collecting layer 11, the structure of the electrode plate includes the current collecting layer 11, the alloy layer 12 and the electrode film layer 20 which are sequentially stacked from bottom to top.

[0050] In the embodiment of the present application, the electrode plate includes a positive electrode plate and a negative electrode plate. In the present application, the positive electrode plate may contain an alloy layer, the negative electrode plate may contain an alloy layer, or both the positive electrode plate and the negative electrode plate may contain an alloy layer. The positive electrode plate containing an alloy layer and the negative electrode plate containing an alloy layer are described below.

[0051] [Negative electrode]

[0052] The negative electrode plate of the secondary battery includes a negative electrode collector layer and a negative electrode film layer attached to the surface of the negative electrode collector layer, the negative electrode collector layer includes a superimposed negative electrode collector layer and an alloy layer, and the alloy layer is close to the negative electrode film layer; the negative electrode film layer includes a negative electrode active material and a binder, and the content of the binder is 0 to 0.4wt% based on the total mass of the negative electrode film layer.

[0053] Among them, the negative electrode current collector layer refers to a structure or part for collecting current, and the negative electrode current collector layer refers to a conventional current collector structure, which can be a metal foil or a composite current collector. For example, as a metal foil, a copper foil can be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0054] In some embodiments, the negative electrode film layer includes a negative electrode active material. The negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0055] Binder refers to a material that plays a bonding role in the negative electrode film layer (making the negative electrode film layer bonded to the negative electrode current collecting layer and bonding the negative electrode active materials to each other), also known as a binder or adhesive. Exemplarily, based on the total mass of the negative electrode film layer, the content of the binder in the negative electrode film layer 20 is 0 (no binder), 0.2wt%, 0.4wt%, or an intermediate value between any of the above two values.

[0056] In some embodiments, the binder includes at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0057] The alloy layer 12 refers to a layer structure containing at least two metal elements. By modifying the negative electrode current collector layer with the alloy layer, the strength and toughness of the negative electrode current collector layer can be improved, and the negative electrode current collector layer can have good conductivity. The present application does not limit the selection of specific metal elements of the alloy layer. As long as the alloy layer structure formed by the metal elements in the negative electrode current collector layer is within the protection scope of the present application. In order to increase the bonding ability between the negative electrode current collector layer and the negative electrode film layer of the secondary battery, a certain amount of binder (for example: 1wt% to 3wt%) is usually added to the negative electrode film layer. Due to the large amount of binder added, the binder is prone to floating. The floating of the binder will block the transmission of lithium ions (or sodium ions), thereby forming a lithium precipitation (or sodium precipitation) problem on the surface of the negative electrode film layer, which will reduce the capacity retention rate of the secondary battery; when lithium precipitation is serious, lithium dendrites (or sodium dendrites) will also appear, which will cause the problem of puncturing the isolation membrane, thereby affecting the safety performance of the secondary battery. The secondary battery provided by the present application adds an alloy layer on the surface of the negative electrode current collecting layer, and arranges a negative electrode film layer on the basis of the alloy layer. The alloy layer has good conductivity, high hardness and toughness, and a certain ability to resist chemical corrosion. The negative electrode current collecting layer can be modified by the alloy layer, the internal resistance of the secondary battery can be reduced, and the bonding strength between the negative electrode film layer and the negative electrode current collecting layer can be improved, thereby reducing the powder falling problem on the basis of reducing or not using a binder in the negative electrode film layer. The amount of binder added is very small or even not added, thereby increasing the amount of active material added to improve the energy density of the secondary battery; in addition, the reduction in binder content can improve the problem of binder floating in the electrode plate, thereby providing more active ion (lithium ion or sodium ion) transmission channels, thereby improving the problem of lithium (or sodium) precipitation on the surface of the negative electrode film layer, so as to improve the capacity retention rate and safety performance of the secondary battery.

[0058] In some embodiments, the tensile strength of the negative electrode sheet is 400Mpa to 900Mpa. The negative electrode current collector layer in the present application contains an alloy layer, which can increase the tensile strength of the negative electrode sheet to 400Mpa to 900Mpa. During the charge and discharge process, even if the secondary battery has a small amount of expansion, the higher strength of the negative electrode sheet can improve the expansion problem, thereby improving the capacity retention rate of the secondary battery. In addition, improving the active ion (lithium ion or sodium ion) transmission channel can effectively improve the lithium (or sodium) precipitation problem, thereby improving the capacity retention rate and safety performance of the secondary battery.

[0059] Among them, the tensile strength of the negative electrode plate refers to: the critical value of the transition of the negative electrode plate from uniform plastic deformation to local concentrated plastic deformation, and it is also the maximum load-bearing capacity of the negative electrode plate under static tensile conditions. The test method for tensile strength is: according to JIS K7127, using the tensile testing machine and automatic recorder AG-A type (trademark) manufactured by Shimadzu, the MD and TD samples (shape; width 10mm × length 100mm) were measured; the sample chuck space is 50mm; the temperature is 23±2℃, the suction cup pressure is 0.30MPa, and the stretching rate is 200mm / min. Exemplarily, the tensile strength of the negative electrode plate is 400Mpa, 500Mpa, 600Mpa, 700Mpa, 800Mpa or 900Mpa, or an intermediate value between any two of the above values. Optionally, the tensile strength of the negative electrode plate is 550Mpa to 750Mpa.

[0060] In some embodiments, the surface roughness Ra of the alloy layer is 15 nm to 50 nm. The bonding strength between the negative electrode film layer and the negative electrode current collector layer can be further improved, and the amount of binder added can be further reduced to further improve the energy density and capacity retention rate of the secondary battery.

[0061] Among them, surface roughness Ra refers to: the surface of the alloy layer has unevenness with small spacing or tiny peaks and valleys, and the distance (wave distance) between two peaks or two valleys is very small (below 1mm). It belongs to the microscopic geometric shape error. The smaller the surface roughness, the smoother the surface. Usually, the morphological features with a wave distance less than 1mm are attributed to surface roughness.

[0062] The surface roughness test method is: using HANDY SURF E-35A (trademark) manufactured by Tokyo Seimitsu Co., Ltd., the surface roughness Ra (arithmetic mean roughness) of the outer surface is measured; the stylus tip uses a diamond 90° cone, 5μmR, and the measurement is carried out under the conditions of evaluation length 5mm, speed 0.6mm / s, sampling length (cut off value) 0.80mm, and load 4mN or less. Exemplarily, the surface roughness of the alloy layer is 15nm, 20nm, 30nm, 40nm or 50nm, or an intermediate value between any two of the above values.

[0063] In some embodiments, in the negative electrode sheet, the adhesion between the negative electrode current collector layer and the negative electrode film layer is 12N / m to 25N / m. The negative electrode current collector contains an alloy layer, which can make the adhesion between the negative electrode current collector and the negative electrode film layer of the negative electrode sheet within the above range, so that in the case of a small amount of binder or no binder, the bonding force between the negative electrode current collector and the negative electrode film layer is basically not affected, so as to reduce the problem of powder falling. In addition, a small amount of binder is added or no binder is added, which can improve the transmission channel of active ions (lithium ions or sodium ions), and can effectively improve the problem of lithium (or sodium) precipitation, thereby improving the capacity retention rate and safety performance of the secondary battery.

[0064] The adhesion between the negative electrode current collector layer and the negative electrode film layer refers to the intermolecular bonding force at the interface between the negative electrode current collector layer and the negative electrode film layer. The adhesion test method is: refer to the national standard GB / T2790-1995 Adhesive 180° Peel Strength Test Method. In specific operation, a tensile machine can be used to perform a 180° peeling force test at a peeling speed of 10mm / min. The peeling force collected when the 60mm negative electrode film layer is completely peeled off from the negative electrode current collector layer is the adhesion between the negative electrode film layer and the negative electrode current collector layer.

[0065] As an example, the adhesion between the negative electrode current collector layer and the negative electrode film layer is 12 N / m, 14 N / m, 16 N / m, 18 N / m, 20 N / m, 22 N / m or 25 N / m, or an intermediate value between any two of the above values.

[0066] In some embodiments, the surface density of the negative electrode sheet is 300 mg / cm 2 ~400mg / cm 2 The negative electrode current collector layer contains an alloy layer, which can improve the compactness of the negative electrode film layer on the alloy layer, so that the surface density of the negative electrode sheet is within the above range, thereby improving the energy density of the secondary battery.

[0067] The surface density of the negative electrode sheet refers to the mass of the negative electrode sheet per unit area. The test method of the surface density is: take a section of the negative electrode sheet, measure the length of the negative electrode sheet as L1, cold-press the negative electrode sheet through a roller, and then measure the length after pressing as L2. The elongation of the negative electrode sheet is (L2-L1) / L1. The surface density is calculated according to the formula = small disc weight / small disc area × (1+elongation) × electrode thickness.

[0068] For example, the surface density of the negative electrode sheet is 300 mg / cm 2 、320mg / cm 2 、340mg / cm 2 、360mg / cm 2 、380mg / cm 2 or 400mg / cm 2 , or any intermediate value between the above two values.

[0069] In some embodiments, the alloy layer contains at least four metal elements, including Co and Ni. The alloy layer contains at least four metal elements, which is a mixture of multiple metals, has a high entropy effect, and can make the alloy layer have the comprehensive properties of high conductivity, high strength, high toughness and chemical corrosion resistance; in addition, it contains Co and Ni elements, which as a current collector layer structure, has more stable electrochemical performance and basically does not undergo chemical reactions during the charge and discharge process.

[0070] Among them, in addition to Co and Ni elements, the alloy layer may also include at least two of Fe, Cu, Ti and Ag elements; this application does not limit it, and other metal elements that can serve as the negative electrode current collector layer may also be added.

[0071] In some embodiments, in the negative electrode sheet, based on the total mass of the alloy layer, the alloy layer includes: Fe: 23wt% to 40wt%, Co: 10wt% to 30wt%, Ni: 20wt% to 35wt%, Cu: 15wt% to 35wt%, C: 7wt% to 15wt%; wherein the carbon can be amorphous carbon, or other carbon materials, such as graphite, carbon black, etc. The composition of the alloy layer of the negative electrode collector layer is within the above range, which can make the tensile strength of the negative electrode sheet higher. In other embodiments, other metals that do not react with the electrolyte and do not react chemically during the charge and discharge process, such as Ti, Ag, etc., can also be added to the alloy layer.

[0072] In some embodiments, the thickness of the negative electrode current collector layer is 4 μm to 15 μm; and / or the thickness of the alloy layer is 10 nm to 50 nm; and / or the thickness of the negative electrode film layer is 25 μm to 100 μm. Through a certain thickness of the negative electrode current collector layer and a certain thickness of the alloy layer, the modification effect of the negative electrode current collector layer is better, so that the conductivity of the negative electrode current collector layer is better, and the internal resistance of the secondary battery can be further reduced; in addition, a certain thickness of the negative electrode film layer can be formed on the current collector layer, and the negative electrode film layer has good adhesion and is not easy to fall off. Optionally, the thickness of the negative electrode film layer is 25 μm to 50 μm.

[0073] In any embodiment, the negative electrode film layer further includes a conductive agent and a dispersant. Based on the total mass of the negative electrode film layer, the negative electrode film layer includes: 96wt% to 99wt% of negative electrode active material, 0.2wt% to 2.8wt% of conductive agent, 0 to 1.5wt% of dispersant, and 0 to 0.4wt% of binder. By increasing and reducing the amount of binder and increasing the content of negative electrode active material, the energy density of the secondary battery can be increased.

[0074] The conductive agent includes at least one of conductive carbon black, conductive graphite, single / multi-walled carbon nanotubes, superconducting carbon, acetylene black, Ketjen black, carbon dots, graphene and carbon nanofibers. The dispersant includes at least one of polyvinyl pyrrolidone (PVP), sodium carboxymethyl cellulose (CMC-Na), lithium carboxymethyl cellulose (CMC-Li), etc. The positive electrode film layer may also optionally include other additives, such as a plasticizer, and the plasticizer may include at least one of BD-3, AP-4plus, etc.

[0075] [Method for preparing negative electrode sheet]

[0076] The preparation method of the above-mentioned negative electrode plate includes: forming a negative electrode film layer on the surface of the negative electrode collector layer by plasma spraying, the negative electrode collector layer includes a superimposed negative electrode collector layer and an alloy layer, the alloy layer is close to the negative electrode film layer, the negative electrode film layer includes a negative electrode active material and a binder, and the content of the binder is 0 to 0.4wt% based on the total mass of the negative electrode film layer.

[0077] Plasma spraying refers to a method of using a plasma arc driven by direct current as a heat source to heat the negative electrode active mixture to a molten or semi-molten state, and spraying it at a high speed onto the surface of the negative electrode collector layer to form a firmly attached negative electrode film layer.

[0078] An alloy layer is added to the surface of the negative electrode current collector layer. The alloy layer has good conductivity, high hardness and toughness, and a certain resistance to chemical corrosion. By modifying the negative electrode current collector layer with the alloy layer, the internal resistance of the secondary battery can be reduced. In addition, due to the high strength and toughness of the alloy layer, an electrode film layer can be formed by plasma spraying. The plasma spraying method melts the surface of the negative electrode active material and forms it on the negative electrode current collector layer, which can increase the density of the negative electrode film layer and improve the bonding ability between the negative electrode film layer and the negative electrode current collector layer. The content of the binder can be reduced to form a negative electrode film layer with a small content or even no binder, and the bonding strength between the negative electrode film layer and the negative electrode current collector layer can still meet the demand, thereby increasing the amount of active material added to improve the energy density of the secondary battery. In addition, the reduction in the binder content can improve the problem of binder floating in the electrode plate, thereby providing more active ion (lithium ion or sodium ion) transmission channels, thereby improving the lithium (or sodium) precipitation problem on the surface of the negative electrode film layer, so as to improve the capacity retention rate and safety performance of the secondary battery.

[0079] Among them, magnetron sputtering can be used to form an alloy layer on the surface of the negative electrode current collector layer. The alloy layer can be formed by the magnetron sputtering method, and a relatively uniform alloy layer can be obtained to further improve the conductivity and strength of the alloy layer. In other embodiments, the alloy layer can also be formed by evaporation, which is not limited in this application.

[0080] The specific method of forming the FeCoNiCu / carbon composite film by the magnetron sputtering method is as follows: using a FeCoNiCu metal splicing target and a carbon target as target materials, using high-purity Ar as the working gas, applying a negative bias voltage to the negative electrode current collector (substrate) after surface cleaning; connecting the FeCoNiCu metal splicing target to a DC power supply, connecting the graphite target to a high-power pulsed magnetron sputtering power supply, starting the power supplies of the two targets at the same time, and co-depositing to prepare the FeCoNiCu / carbon composite film to form an alloy layer.

[0081] In some embodiments, the conditions for plasma spraying to form the negative electrode sheet include: the negative electrode active material of the negative electrode sheet includes a carbon material, and the temperature of the plasma spraying is 1000°C to 3000°C. Spraying the negative electrode active material within the spraying temperature range can form a molten state on the surface of the carbon material so that the bonding strength between the negative electrode current collector layer and the negative electrode film layer is high while being formed on the surface of the negative electrode current collector layer. As an example, the temperature of the plasma spraying is 1000°C, 1500°C, 2000°C, 2500°C or 3000°C. Optionally, the negative electrode active material of the negative electrode sheet includes a carbon material, and the temperature of the plasma spraying is 1500°C to 2000°C.

[0082] In other embodiments, the negative electrode active material further includes other active materials, and the plasma spraying temperature can be adjusted accordingly to achieve the plasma spraying.

[0083] In some embodiments, the conditions for plasma spraying to form the negative electrode sheet include: the spray rate of plasma spraying is 100 g / min to 200 g / min. The spray rate is selected within this range, so that the thickness uniformity of the negative electrode film layer formed on the negative electrode current collector layer can be better. As an example, the spray rate of plasma spraying is 100 g / min, 120 g / min, 140 g / min, 160 g / min, 180 g / min or 200 g / min.

[0084] In some embodiments, the conditions for plasma spraying to form the negative electrode sheet include: along the thickness direction of the negative electrode film layer, the distance between the plasma spraying nozzle and the surface of the negative electrode film layer is 100mm to 250mm. The distance is limited within this range, and the time range for the negative electrode active material to come out of the nozzle to the negative electrode collector layer can be controlled laterally to adjust the state of the molten negative electrode active material during the spraying process, so that the particles of the negative electrode active material are more evenly dispersed, so that the active material of the negative electrode film layer formed on the negative electrode collector layer is more evenly dispersed, the problem of particle adhesion can be improved, and the bonding ability between the negative electrode collector layer and the negative electrode film layer is improved. As an example, along the thickness direction of the negative electrode film layer, the distance between the plasma spraying nozzle and the surface of the negative electrode film layer is 100mm, 150mm, 200mm or 250mm.

[0085] In some embodiments, the conditions for plasma spraying to form the negative electrode sheet include: the spray angle between the spray direction of the plasma spraying and the thickness direction of the negative electrode film layer is 55° to 85°. It can not only make the uniformity of the negative electrode film layer better, but also make the dispersion of the negative electrode active material more uniform, so as to form a negative electrode film layer with better density and uniformity, so as to improve the surface density of the negative electrode sheet and improve the bonding ability between the negative electrode current collector and the negative electrode film layer. As an example, the spray angle between the spray direction of the plasma spraying and the thickness direction of the negative electrode film layer is 55°, 60°, 65°, 70°, 75°, 80° or 85°. Optionally, the spray angle between the spray direction of the plasma spraying and the thickness direction of the negative electrode film layer is 65° to 85°.

[0086] In some embodiments, the method of forming a negative electrode film layer comprises the following steps:

[0087] (1) Stir the raw materials of the negative electrode film layer evenly, wherein the raw materials include 96-99wt% of negative electrode active material, 0.2-2.8wt% of conductive agent, 0-1.5wt% of dispersant, 0-0.4wt% of binder, and a small amount of solvent (the solvent can be NMP, DI-water, etc., which will evaporate during spraying) to obtain powder.

[0088] (2) A plasma spraying device is used to spray the powder onto the surface of the negative electrode current collector layer to form a negative electrode film layer. The working voltage of the plasma spraying device is 2 to 380 V, the current is 1 to 3000 A, and the gas supply pressure is 0.1 to 2 MPa. The plasma flame is used to heat the powder to a molten state on the surface, and the powder is impacted onto the surface of the negative electrode current collector layer to form a coating. The powder is then cooled. Air cooling treatment can be adopted at a temperature of 0 to -10°C for a time of 1 to 30 seconds to obtain a negative electrode sheet.

[0089] As an embodiment, a continuous dry powder mixing device is used in step (1) for processing, and the dry powder raw materials are stirred by rotating the threaded blades outside the first rotating shaft and the second rotating shaft, so that the dry powder raw materials inside the mixing tank are in two stirring environments with different rotation speeds, so that the dry powder raw materials are evenly mixed and the mixing is more complete. At the same time, the threaded blades can fully drive the dry powder raw materials injected into the mixing tank to mix.

[0090] As an implementation mode, the powder in the continuous dry powder mixing equipment in step (1) is transported to a powder feeder through a pipeline, and the powder feeder sends the powder to a spray gun, and the plasma arc emitted by the spray gun sprays the powder onto the negative electrode current collector layer.

[0091] [Positive electrode]

[0092] The positive electrode plate of the secondary battery includes a positive electrode collector layer and a positive electrode film layer attached to the surface of the positive electrode collector layer, the positive electrode collector layer includes a positive electrode collector layer and an alloy layer stacked together, and the alloy layer is close to the positive electrode film layer; the positive electrode film layer includes a positive electrode active material and a binder, and the content of the binder is 0 to 0.4 wt% based on the total mass of the positive electrode film layer.

[0093] Among them, the positive electrode current collector layer refers to a structure or part for collecting current, and the positive electrode current collector layer refers to a conventional current collector structure, which can be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil can be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0094] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0095] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Co c M d O e A fOne or more of lithium transition metal oxides and their modified compounds. 0.8 ≤ a ≤ 1.2, 0.5 ≤ b < 1, 0 < c < 1, 0 < d < 1, 1 ≤ e ≤ 2, 0 ≤ f ≤ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B, and A is selected from one or more of N, F, S, and Cl.

[0096] In some embodiments, by way of example, the positive electrode active material for a lithium-ion battery may include one or more of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), LiNi 0.85 Co 0.15 Al 0.05 O2, LiFePO4, and LiMnPO4.

[0097] In this application, the modified compounds of the above positive electrode active materials may be doping modification and / or surface coating modification of the positive electrode active materials.

[0098] During the charge and discharge process of the battery, the insertion and extraction of Li will occur along with consumption, and the molar content of Li is different when the battery is discharged to different states. In the listing of the positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. When the positive electrode material is applied to the battery system and undergoes charge and discharge cycles, the molar content of Li will change.

[0099] In the listing of the positive electrode materials in this application, the molar content of O is only the theoretical state value, and the release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will show fluctuations.

[0100] In some embodiments, when the secondary battery is a sodium ion battery, the positive electrode active material may be a positive electrode active material for a sodium ion battery known in the art. As an example, the positive electrode active material may include at least one of the following materials: a polyanion compound, a sodium transition metal oxide, a Prussian blue compound, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more.

[0101] Among them, the polyanionic compound can be Li 1+x Mn 1-y A y P 1-z R z O4; wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.

[0102] As an optional technical method of the present application, the polyanionic compound can be Li a A e Mn 1-f B f P 1-g C g O 4-n D n , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo, and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge; C includes one or more elements selected from the group consisting of B, S, Si, and N; D includes one or more elements selected from the group consisting of S, F, Cl, and Br; a is selected from the range of 0.9 to 1.1, e is selected from the range of 0.001 to 0.1, f is selected from the range of 0.001 to 0.5, g is selected from the range of 0.001 to 0.1, n is selected from the range of 0.001 to 0.1, and the second positive electrode active material is electrically neutral.

[0103] As an optional technical method of the present application, the polyanionic compound can be Na 4+x R 3-y P 4-m O 15 / C; wherein, 0 < x < 0.5, 0 < y ≤ 0.5, 0 < m ≤ 0.2, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Cr, Nb, Mo, In, Ga, Sn, Hf, Ta, W, and Pb.

[0104] As an optional technical solution of the present application, the polyanionic compound may be Na x-a A a V y-b M b (PO4) 2-2c (DO4) 2c F z-d Q d , wherein the A element represents an alkali metal element that dopes and replaces the Na element, the M element represents a metal element that replaces the V element, the D element represents a doping element that replaces the P element, the Q element represents a doping element that replaces the F element, the D element includes at least one of Si and S, the Q element includes at least one of Cl and O; 3.5 ≤ x ≤ 4.5, 0 ≤ a ≤ 0.15x, 0.8 ≤ y ≤ 1.1, 0 ≤ b ≤ 0.3y, 0 ≤ c ≤ 0.15, 0.8 ≤ z ≤ 1.1, 0 ≤ d ≤ 0.2z. Optionally, the A element includes at least one of K and Li; the M element includes at least one of Fe, Cr, Al, Sc, Ga, In, Ti, Zr, Mn, Zn, Ni, Cu, and Co.

[0105] In the sodium transition metal compound, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, and V, and 0 < x ≤ 1.

[0106] The Prussian blue compound may be a class of compounds having sodium ions, transition metal ions, and cyanide ions (CN - ). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. The Prussian blue compound is, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Mn, Fe, Ni, Co, Cu, and Zn, 0 < a ≤ 2, 0 < b < 1, 0 < c < 1.

[0107] Binder refers to a material that plays a bonding role in the positive electrode film layer (making the positive electrode film layer bonded to the positive electrode current collecting layer and bonding the positive electrode active materials to each other), also known as a binder or adhesive. Exemplarily, the content of the binder in the electrode film layer 20 is 0 (no binder), 0.2wt%, 0.4wt%, or an intermediate value between any of the above two values.

[0108] The binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0109] The alloy layer 12 refers to a layer structure containing at least two metal elements. By modifying the positive electrode current collector layer with the alloy layer, the strength and toughness of the positive electrode current collector layer can be improved, and the positive electrode current collector layer can have good conductivity. The present application does not limit the selection of specific metal elements of the alloy layer. As long as the alloy layer structure can be formed by the metal elements in the positive electrode current collector layer, it is within the protection scope of the present application.

[0110] In the prior art, in order to increase the bonding ability between the positive current collector layer and the positive electrode film layer of the secondary battery, a certain amount of binder (for example, 1wt% to 3wt%) is usually added to the positive electrode film layer. Due to the large amount of binder added, the binder is prone to floating. The floating of the binder will reduce the transmission channel of the active ions (lithium ions or sodium ions), thereby reducing the capacity retention rate of the secondary battery. The secondary battery provided by the present application adds an alloy layer on the surface of the positive electrode current collecting layer, and arranges an electrode film layer on the basis of the alloy layer. The alloy layer has good conductivity, high hardness and toughness, and a certain ability to resist chemical corrosion. The positive electrode current collecting layer can be modified by the alloy layer, the internal resistance of the secondary battery can be reduced, and the bonding strength between the positive electrode film layer and the positive electrode current collecting layer can be improved, thereby reducing the powder falling problem on the basis of reducing or not using the binder in the positive electrode film layer. The amount of binder added is very little or even no, thereby increasing the amount of positive electrode active material added to improve the energy density of the secondary battery; in addition, the reduction in binder content can improve the problem of binder floating in the positive electrode plate, thereby providing more active ion (lithium ion or sodium ion) transmission channels from the positive electrode film layer to the isolation membrane, thereby increasing the capacity retention rate of the secondary battery.

[0111] In any embodiment, the electrode plate includes a positive electrode plate, and the tensile strength of the positive electrode plate is 200Mpa to 400Mpa. The tensile strength of the positive electrode plate is relatively high. During the charge and discharge process, even if the secondary battery has a small amount of expansion, the expansion problem can be improved due to the high strength of the positive electrode plate, thereby improving the capacity retention rate of the secondary battery.

[0112] Among them, the tensile strength of the positive electrode plate refers to: the critical value of the transition of the positive electrode plate from uniform plastic deformation to local concentrated plastic deformation, and it is also the maximum load-bearing capacity of the positive electrode plate under static tensile conditions. The test method for tensile strength is: according to JIS K7127, using the tensile testing machine and automatic recorder AG-A type (trademark) manufactured by Shimadzu Corporation, MD and TD samples (shape; width 10mm × length 100mm) were measured; the sample chuck space is 50mm; the temperature is 23±2℃, the suction cup pressure is 0.30MPa, and the stretching rate is 200mm / min. Exemplarily, the tensile strength of the positive electrode plate is 200Mpa, 250Mpa, 300Mpa, 350Mpa or 400Mpa, or an intermediate value between any two of the above values.

[0113] In any embodiment, the surface roughness Ra of the alloy layer is 15nm to 50nm. When the surface roughness of the alloy layer is within the above range, the bonding strength between the positive electrode film layer and the positive electrode current collector layer can be further improved, and the amount of binder added can be further reduced to further improve the energy density and capacity retention rate of the secondary battery.

[0114] Among them, surface roughness Ra refers to: the surface of the alloy layer has unevenness with small spacing or tiny peaks and valleys, and the distance (wave distance) between two peaks or two valleys is very small (below 1mm). It belongs to the microscopic geometric shape error. The smaller the surface roughness, the smoother the surface. Usually, the morphological features with a wave distance less than 1mm are attributed to surface roughness.

[0115] The surface roughness test method is: using HANDY SURF E-35A (trademark) manufactured by Tokyo Seimitsu Co., Ltd., the surface roughness Ra (arithmetic mean roughness) of the outer surface is measured; the stylus tip uses a diamond 90° cone, 5μmR, and the measurement is carried out under the conditions of evaluation length 5mm, speed 0.6mm / s, sampling length (cut off value) 0.80mm, and load 4mN or less. Exemplarily, the surface roughness of the alloy layer is 15nm, 20nm, 30nm, 40nm or 50nm, or an intermediate value between any two of the above values.

[0116] In any embodiment, in the positive electrode sheet, the bonding force between the positive electrode collector layer and the positive electrode film layer is 15N / m to 50N / m. The positive electrode collector contains an alloy layer, which can make the bonding force between the positive electrode collector and the positive electrode film layer of the positive electrode sheet within the above range, so that in the case of a small amount of binder or no binder, the bonding force between the positive electrode collector and the positive electrode film layer is basically not affected, thereby reducing the problem of powder falling.

[0117] The adhesion between the positive electrode current collector layer and the positive electrode film layer refers to the intermolecular bonding force at the interface between the positive electrode current collector layer and the positive electrode film layer. The adhesion test method is as follows: refer to the national standard GB / T2790-1995 Adhesive 180° Peel Strength Test Method. In specific operation, a 180° peeling force test can be performed using a tensile machine at a peeling speed of 10mm / min. The peeling force collected when the 60mm positive electrode film layer is completely peeled off from the positive electrode current collector layer is the adhesion between the positive electrode film layer and the positive electrode current collector layer.

[0118] As an example, the adhesion between the positive current collector layer and the positive electrode film layer is 15N / m, 20N / m, 25N / m, 30N / m, 35N / m, 40N / m, 45N / m or 50N / m, or an intermediate value between any two of the above values. Optionally, the adhesion between the positive current collector layer and the positive electrode film layer is 30N / m to 45N / m.

[0119] In any embodiment, the surface density of the positive electrode sheet is 500 mg / cm 2 ~1000mg / cm 2 The positive electrode current collector contains an alloy layer, which can improve the compactness of the positive electrode film layer on the alloy layer, so that the surface density of the positive electrode sheet is within the above range, thereby improving the energy density of the secondary battery.

[0120] The surface density of the positive electrode sheet refers to the mass of the positive electrode sheet per unit area. The test method of the surface density is: take a section of the positive electrode sheet, measure the length of the positive electrode sheet as L3, cold-press the positive electrode sheet through a roller, and then measure the length after pressing as L4. The elongation of the positive electrode sheet is (L3-L4) / L3. The surface density is calculated according to the formula = small disc weight / small disc area × (1+elongation) × electrode thickness.

[0121] For example, the surface density of the positive electrode sheet is 500 mg / cm 2 、550mg / cm 2 、600mg / cm 2 、650mg / cm 2 、700mg / cm 2 、750mg / cm 2 、800mg / cm 2 、850mg / cm 2 、900mg / cm 2 、950mg / cm 2 or 1000mg / cm 2 , or any intermediate value between the above two values. Optionally, the surface density of the positive electrode sheet is 700 mg / cm 2 ~850mg / cm 2 .

[0122] In any embodiment, the alloy layer contains at least four metal elements, including Co and Ni. The alloy layer contains at least four metal elements, which is a mixture of multiple metals, has a high entropy effect, and can make the alloy layer have the comprehensive properties of high conductivity, high strength, high toughness and chemical corrosion resistance; in addition, it contains Co and Ni elements, which as a current collector layer structure, has more stable electrochemical performance and basically does not undergo chemical reactions during the charge and discharge process.

[0123] Among them, in addition to Co and Ni elements, the alloy layer may also include at least two of Fe, Al, Ti and Ag elements; this application does not limit it, and other metal elements that can serve as the positive electrode current collector layer may also be added.

[0124] In any embodiment, in the positive electrode sheet, based on the total mass of the alloy layer, the alloy layer includes: Al: 7wt% to 9wt%, Fe: 16wt% to 19wt%, Co: 16wt% to 20wt%, Ni: 14wt% to 20wt%, Li: 15wt% to 21wt%. The composition of the alloy layer of the positive electrode collector layer is within the above range, which can make the tensile strength of the positive electrode sheet higher. In other embodiments, other metals that do not react with the electrolyte and do not react chemically during the charge and discharge process, such as Ti, Ag, etc., can also be added to the alloy layer.

[0125] In any embodiment, the thickness of the positive current collector layer is 4μm to 15μm; and / or, the thickness of the alloy layer is 10nm to 50nm; and / or, the thickness of the positive film layer is 25μm to 100μm. Through a certain thickness of the positive current collector layer and a certain thickness of the alloy layer, the modification effect of the positive current collector layer is better, so that the conductivity of the positive electrode fluid layer is better, and the internal resistance of the secondary battery can be further reduced; in addition, a certain thickness of the positive film layer can be formed on the positive current collector layer, and the positive film layer has good adhesion and is not easy to fall off. Optionally, the thickness of the positive film layer is 50μm to 100μm.

[0126] In any embodiment, the positive electrode film layer further includes a conductive agent and a dispersant. Based on the total mass of the positive electrode film layer, the positive electrode film layer includes: 96wt% to 99wt% positive electrode active material, 0.2wt% to 2.8wt% conductive agent, 0 to 1.5wt% dispersant, and 0 to 0.4wt% binder. By increasing and reducing the amount of binder and increasing the content of positive electrode active material, the energy density of the secondary battery can be increased.

[0127] The conductive agent includes at least one of conductive carbon black, conductive graphite, single / multi-walled carbon nanotubes, superconducting carbon, acetylene black, Ketjen black, carbon dots, graphene and carbon nanofibers. The dispersant includes at least one of polyvinyl pyrrolidone (PVP), sodium carboxymethyl cellulose (CMC-Na), lithium carboxymethyl cellulose (CMC-Li), etc. The positive electrode film layer may also optionally include other additives, such as a plasticizer, and the plasticizer may include at least one of BD-3, AP-4plus, etc.

[0128] [Method for preparing positive electrode sheet]

[0129] The preparation method of the above-mentioned positive electrode plate includes: using plasma spraying to form a positive electrode film layer on the surface of the positive electrode collector layer, the positive electrode collector layer includes a superimposed positive electrode collector layer and an alloy layer, the alloy layer is close to the positive electrode film layer, the positive electrode film layer includes a positive electrode active material and a binder, and the content of the binder is 0 to 0.4wt% based on the total mass of the positive electrode film layer.

[0130] Plasma spraying refers to a method of using a plasma arc driven by direct current as a heat source to heat the positive electrode active mixture to a molten or semi-molten state, and spraying it at a high speed onto the surface of the positive electrode collector layer to form a firmly attached positive electrode film layer.

[0131] An alloy layer is added to the surface of the positive current collecting layer. The alloy layer has good conductivity, high hardness and toughness, and a certain resistance to chemical corrosion. By modifying the positive current collecting layer with the alloy layer, the internal resistance of the secondary battery can be reduced. In addition, due to the high strength and toughness of the alloy layer, a positive electrode film layer can be formed by plasma spraying. The plasma spraying method melts the surface of the positive electrode active material and forms it on the positive current collecting layer, which can increase the density of the positive electrode film layer and improve the bonding ability between the positive electrode film layer and the positive current collecting layer. The content of the binder can be reduced to form a positive electrode film layer with less or even no binder, and the bonding strength between the positive electrode film layer and the positive current collecting layer can still meet the demand, thereby increasing the amount of positive electrode active material added to improve the energy density of the secondary battery. In addition, the reduction in the binder content can improve the problem of binder floating in the positive electrode sheet, thereby providing more active ion (lithium ion or sodium ion) transmission channels to improve the capacity retention rate and safety performance of the secondary battery.

[0132] Among them, magnetron sputtering can be used to form an alloy layer on the surface of the positive current collector layer. The alloy layer can be formed by the magnetron sputtering method, and a relatively uniform alloy layer can be obtained to further improve the conductivity and strength of the alloy layer. In other embodiments, the alloy layer can also be formed by evaporation, which is not limited in this application.

[0133] The specific method of forming the FeCoNiAl / Li composite film by the magnetron sputtering method is as follows: using a FeCoNiAl metal splicing target and a lithium target as target materials, using high-purity Ar as the working gas, applying a negative bias voltage to the positive electrode current collector (substrate) after surface cleaning; connecting the FeCoNiAl metal splicing target to a DC power supply, connecting the lithium target to a high-power pulsed magnetron sputtering power supply, starting the power supplies of the two targets at the same time, and co-depositing to prepare the FeCoNiAl / Li composite film to form an alloy layer.

[0134] In some embodiments, the conditions for plasma spraying to form the positive electrode sheet include: the temperature of plasma spraying is 800°C to 1500°C. Spraying the positive electrode active material within the range of the spraying temperature can form a molten state on the surface of the positive electrode active material so that it is formed on the surface of the positive electrode collector layer while making the bonding strength between the positive electrode collector layer and the positive electrode film layer higher. As an example, the temperature of plasma spraying is 800°C, 900°C, 1000°C, 1200°C or 1500°C. The selection of different positive electrode active materials has little effect on the temperature of plasma spraying, as long as the temperature of plasma spraying can be achieved, it is within the protection scope of this application.

[0135] In some embodiments, the conditions for plasma spraying to form the positive electrode sheet include: the spray rate of plasma spraying is 100 g / min to 200 g / min. The spray rate is selected within this range, which can make the thickness uniformity of the positive electrode film layer formed on the positive electrode current collector layer better. As an example, the spray rate of plasma spraying is 100 g / min, 120 g / min, 140 g / min, 160 g / min, 180 g / min or 200 g / min.

[0136] In some embodiments, the conditions for plasma spraying to form the positive electrode sheet include: along the thickness direction of the positive electrode film layer, the distance between the plasma spraying nozzle and the surface of the positive electrode film layer is 100mm to 250mm. The distance is limited within this range, and the time range for the negative electrode active material to come out of the nozzle to the positive electrode collector layer can be controlled laterally to adjust the state of the molten positive electrode active material during the spraying process, so that the particles of the positive electrode active material are more evenly dispersed, so that the positive electrode active material of the positive electrode film layer formed on the positive electrode collector layer is more evenly dispersed, the problem of particle adhesion can be improved, and the bonding ability between the positive electrode collector layer and the positive electrode film layer is improved. As an example, along the thickness direction of the positive electrode film layer, the distance between the plasma spraying nozzle and the surface of the positive electrode film layer is 100mm, 150mm, 200mm or 250mm.

[0137] In some embodiments, the conditions for plasma spraying to form the positive electrode sheet include: the spray angle between the spray direction of the plasma spraying and the thickness direction of the positive electrode film layer is 55° to 85°. Not only can the uniformity of the positive electrode film layer be better, but also the dispersion of the positive electrode active material can be more uniform, so as to form a positive electrode film layer with better density and uniformity, so as to improve the surface density of the positive electrode sheet and the bonding ability between the positive electrode current collector and the positive electrode film layer. As an example, the spray angle between the spray direction of the plasma spraying and the thickness direction of the positive electrode film layer is 55°, 60°, 65°, 70°, 75°, 80° or 85°. Optionally, the spray angle between the spray direction of the plasma spraying and the thickness direction of the positive electrode film layer is 65° to 85°.

[0138] In some embodiments, the method of forming a positive electrode film layer comprises the following steps:

[0139] (1) Stir the raw materials of the positive electrode film layer evenly, wherein the raw materials include 96-99wt% positive electrode active material, 0.2-2.8wt% conductive agent, 0-1.5wt% dispersant, 0-0.4wt% binder, and a small amount of solvent (the solvent can be NMP, DI-water, etc., which will evaporate during spraying) to obtain a powder.

[0140] (2) The powder is sprayed onto the surface of the positive electrode current collector layer by a plasma spraying device to form a positive electrode film layer. The working voltage of the plasma spraying device is 2 to 380 V, the current is 1 to 3000 A, and the gas supply pressure is 0.1 to 2 MPa. The powder is heated to a molten state by a plasma flame, and then impacted onto the surface of the positive electrode current collector layer to form a coating. The powder is then cooled. Air cooling treatment can be adopted at a temperature of 0 to -10°C for a time of 1 to 30 seconds to obtain a positive electrode sheet.

[0141] As an embodiment, a continuous dry powder mixing device is used in step (1) for processing, and the dry powder raw materials are stirred by rotating the threaded blades outside the first rotating shaft and the second rotating shaft, so that the dry powder raw materials inside the mixing tank are in two stirring environments with different rotation speeds, so that the dry powder raw materials are evenly mixed and the mixing is more complete. At the same time, the threaded blades can fully drive the dry powder raw materials injected into the mixing tank to mix.

[0142] As an implementation mode, the powder in the continuous dry powder mixing equipment in step (1) is transported to a powder feeder through a pipeline, and the powder feeder sends the powder to a spray gun, and the plasma arc emitted by the spray gun sprays the powder onto the positive electrode current collector layer.

[0143] [Secondary battery]

[0144] The embodiment of the present application provides a secondary battery. The present application has no particular limitation on the type of the secondary battery, for example, the secondary battery may be a lithium ion battery or a sodium ion battery.

[0145] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0146] The positive electrode sheet adopts the positive electrode sheet provided in the embodiment of the present application, and / or the negative electrode sheet adopts the negative electrode sheet provided in the embodiment of the present application, so that the secondary battery of the present application has high battery performance.

[0147] The present application has no particular restrictions on the type of electrolyte, which can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte). A secondary battery using an electrolyte, and some secondary batteries using a solid electrolyte.

[0148] The positive electrode plate can also be a conventional positive electrode plate, which includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0149] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0150] The negative electrode plate may also be a conventional negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector.

[0151] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0152] [Electrolytes]

[0153] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0154] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0155] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0156] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0157] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0158] [Isolation film]

[0159] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0160] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0161] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0162] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0163] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0164] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 2 The battery cell 5 is a square structure as an example.

[0165] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0166] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0167] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0168] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0169] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0170] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0171] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0172] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0173] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0174] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0175] Example

[0176] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0177] Example 1-1

[0178] 1) Preparation of positive electrode

[0179] The mass ratio of the positive electrode active material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1O2), 0.7% conductive carbon black, and 1.9% binder PVDF were mixed, and solvent NMP was added. The mixture was stirred and mixed to obtain a positive electrode slurry, which was then extruded and coated on both surfaces of a positive electrode current collector aluminum foil with a thickness of 12 μm. The coating weight per unit area of ​​the positive electrode film was 0.250 g / 1540.25 mm 2 (measured by weight excluding solvent), and then dried and cold pressed to obtain a positive electrode sheet.

[0180] 2) Preparation of negative electrode sheet

[0181] Using FeCoNiCu metal splicing target and graphite target as target materials, high-purity Ar as working gas, a negative bias voltage is applied to the two surfaces of the negative electrode current collector layer copper foil with a thickness of 10 μm after surface cleaning, the FeCoNiCu metal splicing target is connected to a DC power supply, the graphite target is connected to a high-power pulsed magnetron sputtering power supply, the power supplies of the two targets are started at the same time, and a FeCoNiCu / graphite composite film is co-deposited as an alloy layer (for specific thickness, see Table 1), wherein the composition of the alloy layer includes: Fe content of 30wt%, Co content of 10wt%, Ni content of 30wt%, Cu content of 20wt%, and C content of 10wt%, to obtain a negative electrode current collector layer.

[0182] 98.8% of negative electrode active material graphite, 0.5% of dispersant CMC sodium carboxymethyl cellulose, and 0.7% of conductive agent carbon nanotubes are mixed evenly using a continuous dry powder mixing device to obtain dry powder.

[0183] The working voltage of the plasma spraying equipment is 200V, the current is 1000A, and the gas supply pressure is 1Mpa. The plasma flame heats the evenly stirred powder to a molten state, and uses the plasma flame to impact the surface of the alloy layer of the negative electrode current collector to form a coating with a thickness of 35μm (see Table 1 for specific plasma spraying parameters), and then air-cooling treatment is performed at a temperature of -5°C for 20s to form a negative electrode film layer to obtain a negative electrode sheet.

[0184] 3) Isolation film

[0185] A polyethylene porous membrane was used as the isolation membrane.

[0186] 4) Electrolyte

[0187] 1M LiPF6 is dissolved in a solution with a composition of EC:EMC:DMC=1:1:1.

[0188] 5) Preparation of secondary batteries

[0189] Cold pressing → pre-slitting → slitting → winding → shaping → adapter welding → ultrasonic welding → mylar packing → shelling → top cover welding → baking → liquid filling → forming → capacity → lower warehouse.

[0190] The composition of the alloy layer of the secondary battery of Examples 1-2 to 1-6 is the same as that of the alloy layer of Example 1-1, and will not be repeated here. The difference between the secondary batteries of Examples 1-2 to 1-6 and the secondary battery of Example 1-1 is that the thickness of the alloy layer is different, the binder content in the negative electrode powder is different, and the spraying process of the negative electrode film layer is different, see Table 1 for details. Among them, Example 1-2 adds 0.4% of the binder polymethacrylic acid, and the added content of the negative electrode active material graphite is 98%.

[0191] The negative electrode current collector layer of the negative electrode plate in Comparative Example 1 does not contain an alloy layer. The preparation method of the negative electrode plate in Comparative Example 1 is: 96.3% of negative electrode active material graphite, 0.5% of dispersant sodium carboxymethyl cellulose, 0.4% of conductive agent carbon nanotubes, and 2.8% of binder SBR are mixed in a mass ratio, deionized water as a solvent is added, and the mixture is fully stirred to obtain a negative electrode slurry, which is then extruded and coated on both surfaces of a negative electrode current collector copper foil with a thickness of 10 μm, and the negative electrode plate is obtained after drying and cold pressing.

[0192] Table 1 Parameters of negative electrode sheets of Examples 1-1 to 1-6 and Comparative Example 1

[0193]

[0194] Among them, the performance test method of the negative electrode is as follows:

[0195] (1) Tensile strength test:

[0196] The secondary battery was disassembled, and the negative electrode piece of the secondary battery was taken out. According to JIS K7127, the MD and TD samples (shape; width 10 mm × length 100 mm) were measured using a tensile testing machine and automatic recorder AG-A (trademark) manufactured by Shimadzu Corporation; the chuck space of the sample was 50 mm; the temperature was 23±2°C, the suction cup pressure was 0.30 MPa, and the stretching rate was 200 mm / min. The critical tensile force when the negative electrode piece broke was tested to obtain the tensile strength.

[0197] (2) Adhesion test:

[0198] The secondary battery was disassembled, and the negative electrode sheet of the secondary battery was taken. According to the national standard GB / T2790-1995 adhesive 180° peel strength test method, the two surfaces of the negative electrode sheet were respectively adhered to two steel plates by double-sided tape. The two jaws of the tensile testing machine were respectively clamped with two steel plates. The tensile testing machine was used to perform a 180° peel force test at a peeling speed of 10 mm / min. The peeling force collected when the 60 mm negative electrode film layer was completely peeled off from the negative electrode current collector layer was the bonding force between the negative electrode film layer and the negative electrode current collector layer.

[0199] (3) Surface density test:

[0200] Disassemble the secondary battery, take the negative electrode sheet of the secondary battery, measure the length of the negative electrode sheet as L1, cold-press the negative electrode sheet through a roller, and then measure the length after pressing as L2. The elongation of the negative electrode sheet is (L2-L1) / L1. Take a small disc and calculate the surface density according to the formula = small disc weight / small disc area × (1+elongation) × electrode sheet thickness.

[0201] (4) Surface roughness test:

[0202] Disassemble the secondary battery, take the negative electrode piece of the secondary battery, soak the negative electrode piece in alcohol to remove the negative electrode film layer, and obtain the negative electrode collector layer. Use HANDY SURF E-35A (trademark) manufactured by Tokyo Seimitsu Co., Ltd. to measure the surface roughness Ra of the outer surface of the negative electrode collector layer (the average roughness is calculated by uniformly testing 10 points); use a diamond 90° cone and 5μmR at the front end of the stylus, and measure under the conditions of evaluation length 5mm, speed 0.6mm / s, sampling length (cut off value) 0.80mm, and load less than 4mN.

[0203] In addition, the secondary batteries of Examples 1-1 to 1-6 and Comparative Example 1 were subjected to performance tests and the results are shown in Table 2.

[0204] (1) DCR test (DC internal resistance):

[0205] Capacity test: the lower warehouse battery cells (with clamps) are first calibrated at a temperature of -25°C, and then pulse discharge is performed to obtain the DC impedance diagram during the discharge process. The DCR value of the ordinate at 50% SOC and the DCR value of the ordinate at 10% SOC are taken on the DC impedance diagram during the discharge process to obtain the DCR of 50% SOC and the DCR of 10% SOC.

[0206] (2) Capacity retention rate:

[0207] The capacity retention rate after 600 cycles at 45°C was tested respectively;

[0208] Capacity retention after 1000 cycles at 25°C.

[0209] Under a constant temperature environment of 25°C, at a voltage of 2.5-4.43V, charge to 4.43V at a rate of 0.33C, then charge at a constant voltage at 4.43V to a current ≤0.05mA, let stand for 5 minutes, then discharge to 2.5V at a rate of 0.2C, and record the discharge capacity; repeat the previous process to obtain the capacity retention rate after 1000 cycles, capacity retention rate = first cycle discharge capacity / discharge capacity at a specified number of cycles × 100%, i.e., battery cell cycle retention rate (%).

[0210] At a temperature of 45°C, the capacity retention rate test method after 600 cycles is as follows: in a constant temperature environment of 45°C, at a voltage of 2.5-4.43V, charge to 4.43V at a rate of 0.5C, then charge at a constant voltage at 4.43V to a current ≤0.05mA, let stand for 5 minutes, then discharge to 2.5V at a rate of 0.2C, and record the discharge capacity; repeat the previous process to obtain the capacity retention rate after 600 cycles, capacity retention rate = first cycle discharge capacity / discharge capacity at a specified number of cycles × 100%, that is, the battery cell cycle retention rate (%).

[0211] (3) Powder loss

[0212] Battery vibration test: after disassembly, check the powder falling inside the aluminum shell and determine the degree of powder falling.

[0213] The judgment standard is to judge the degree of powder falling according to whether there is deposition on the bottom of the aluminum shell: slight means that the powder falling coverage rate of the bottom wall of the aluminum shell is less than 10%; small amount means that the powder falling coverage rate of the bottom wall of the aluminum shell is 10% to 30%.

[0214] After testing, the powder shedding of the secondary batteries of Examples 1-1 to 1-6 and Comparative Example 1 was slight, indicating that in the present application, the addition of a small amount of binder, or no addition of binder, still basically does not cause the problem of powder shedding, and the bonding performance can meet the requirements.

[0215] Figure 8 A cross-sectional scanning electron microscope image of the negative electrode sheet provided in Example 1-1 of the present application; Fig. 9 This is a cross-sectional scanning electron microscope image of the negative electrode sheet provided in Comparative Example 1 of the present application. Figure 8 and Fig. 9 By comparison, it can be seen that the distribution of the negative electrode active material in the negative electrode film layer of the negative electrode plate provided in the comparative example of the present application is in a granular state, and its density is relatively low; while the distribution of the negative electrode active material in the negative electrode film layer of the negative electrode plate provided in the embodiment of the present application is relatively uniform, and based on plasma melt spraying, the surface of part of the active material can be melted and bonded and distributed, with high density, thereby increasing the surface density of the negative electrode plate.

[0216] Table 2 Performance results of Examples 1-1 to 1-6 and Comparative Example 1

[0217]

[0218] Combining Table 1 and Table 2, it can be seen that the battery performance of Examples 1-1 to 1-6 is better than that of Comparative Example 1, as shown in that the DCR of the battery discharged at a low temperature of -25°C is significantly improved compared with Comparative Example 1, indicating that the DC internal resistance of the secondary battery is reduced and the capacity retention rate is higher.

[0219] Example 2-1

[0220] 1) Preparation of positive electrode

[0221] Using FeCoNiAl metal splicing target and lithium target as target materials, high-purity Ar as working gas, a negative bias is applied to the two surfaces of the positive electrode current collector aluminum foil with a thickness of 12 μm after surface cleaning, the FeCoNiAl metal splicing target is connected to a DC power supply, the lithium target is connected to a high-power pulsed magnetron sputtering power supply, and the power supplies of the two targets are started at the same time to co-deposit and prepare a FeCoNiAl / Li composite film as an alloy layer (see Table 3 for specific thickness), wherein the composition of the alloy layer includes: Fe content of 25wt%, Co content of 20wt%, Ni content of 15wt%, Al content of 20wt%, and Li content of 20wt%, to obtain a positive electrode current collector layer.

[0222] The mass ratio is 99.3% of the positive electrode active material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O2), 0.7% conductive agent conductive carbon black, and stir evenly using a continuous dry powder stirring equipment to obtain dry powder.

[0223] The working voltage of the plasma spraying equipment is 200V, the current is 1000A, and the gas supply pressure is 1Mpa. The plasma flame heats the evenly stirred powder to a molten state, and uses the plasma flame to impact the surface of the alloy layer of the positive electrode current collecting layer to form a coating with a thickness of 75μm (see Table 3 for specific plasma spraying parameters), and then air-cooling treatment is performed at a temperature of -5°C for 20s to form a positive electrode film layer to obtain a positive electrode sheet.

[0224] 2) Preparation of negative electrode sheet

[0225] A negative electrode active material graphite having a mass ratio of 96.3%, a dispersant sodium carboxymethyl cellulose having a mass ratio of 0.5%, a conductive agent carbon nanotube having a mass ratio of 0.4%, and a binder SBR having a mass ratio of 2.8% are mixed, deionized water as a solvent is added, and the mixture is stirred and mixed thoroughly to obtain a negative electrode slurry, which is then extruded and coated on both surfaces of a negative electrode current collector copper foil having a thickness of 10 μm, and the negative electrode sheet is obtained after drying and cold pressing.

[0226] 3) Isolation film

[0227] A polyethylene porous membrane was used as the isolation membrane.

[0228] 4) Electrolyte

[0229] 1M LiPF6 is dissolved in a solution with a composition of EC:EMC:DMC=1:1:1.

[0230] 5) Preparation of secondary batteries

[0231] Cold pressing → pre-slitting → slitting → winding → shaping → adapter welding → ultrasonic welding → mylar packing → shelling → top cover welding → baking → liquid filling → forming → capacity → lower warehouse.

[0232] The composition of the alloy layer of the secondary battery of Examples 2-2 to 2-5 is the same as that of the alloy layer of Example 2-1, which will not be repeated here. The secondary batteries of Examples 2-2 to 2-5 are different from the secondary battery of Example 2-1 in that the thickness of the alloy layer is different and the spraying process of the negative electrode film layer is different, see Table 3 for details.

[0233] The positive electrode current collector layer of the positive electrode sheet in Comparative Example 2 does not contain an alloy layer. The preparation method of the positive electrode sheet in Comparative Example 2 is as follows: 0.8 Co 0.1 Mn 0.1 O2), 0.7% conductive carbon black, and 1.9% binder PVDF were mixed, and solvent NMP was added. The mixture was stirred and mixed to obtain a positive electrode slurry, which was then extruded and coated on both surfaces of a positive electrode current collector aluminum foil with a thickness of 12 μm. The coating weight per unit area of ​​the positive electrode film was 0.250 g / 1540.25 mm 2 (measured by weight excluding solvent), and then dried and cold pressed to obtain a positive electrode sheet.

[0234] Table 3 Parameters of positive electrode sheets of Examples 2-1 to 2-5 and Comparative Example 2

[0235]

[0236] Among them, the performance test method of the positive electrode is as follows:

[0237] (1) Tensile strength test:

[0238] The secondary battery was disassembled, and the positive electrode piece of the secondary battery was taken out. According to JIS K7127, the MD and TD samples (shape; width 10 mm × length 100 mm) were measured using a tensile testing machine and automatic recorder AG-A (trademark) manufactured by Shimadzu Corporation; the chuck space of the sample was 50 mm; the temperature was 23±2°C, the suction cup pressure was 0.30 MPa, and the stretching rate was 200 mm / min. The critical tensile force when the positive electrode piece broke was tested to obtain the tensile strength.

[0239] (2) Adhesion test:

[0240] Disassemble the secondary battery, take the positive electrode sheet of the secondary battery, and according to the national standard GB / T2790-1995 adhesive 180° peel strength test method, use double-sided tape to stick the two surfaces of the negative electrode sheet to two steel plates respectively. The two jaws of the tensile testing machine are respectively clamped with two steel plates. The tensile testing machine is used to perform a 180° peel force test at a peeling speed of 10 mm / min. The peeling force collected when the 60 mm negative electrode film layer is completely peeled off from the positive electrode current collector layer is the bonding force between the positive electrode film layer and the positive electrode current collector layer.

[0241] (3) Surface density test:

[0242] Disassemble the secondary battery, take the positive electrode sheet of the secondary battery, measure the length of the positive electrode sheet as L3, cold-press the positive electrode sheet through a roller, and then measure the length after pressing as L4. The elongation of the negative electrode sheet is (L4-L3) / L3. Take the small disc and calculate the surface density according to the formula = small disc weight / small disc area × (1+elongation) × electrode sheet thickness.

[0243] (4) Surface roughness test:

[0244] Disassemble the secondary battery, take the positive electrode plate of the secondary battery, soak the positive electrode plate in diethyl carbonate to remove the positive electrode film layer, and obtain the positive electrode collector layer. Use HANDY SURF E-35A (trademark) manufactured by Tokyo Seimitsu Co., Ltd. to measure the surface roughness Ra of the outer surface of the positive electrode collector layer (the average roughness is calculated by uniformly testing 10 points); use a diamond 90° cone and 5μmR at the front end of the stylus, and measure under the conditions of evaluation length 5mm, speed 0.6mm / s, sampling length (cut off value) 0.80mm, and load less than 4mN.

[0245] In addition, the test methods for the performance of the secondary batteries of the above-mentioned Examples 2-1 to 2-5 and Comparative Example 2 refer to those of Example 1-1 and are not described again. The results are shown in Table 4.

[0246] Table 4 Performance results of Examples 2-1 to 2-5 and Comparative Example 2

[0247]

[0248]

[0249] Combining Table 3 and Table 4, it can be seen that the battery performance of Examples 2-1 to 2-5 is better than that of Comparative Example 2, as shown in that the DCR of the battery discharged at a low temperature of -25°C is significantly improved compared with Comparative Example 2, indicating that the DC internal resistance of the secondary battery is reduced and the capacity retention rate is higher.

[0250] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A secondary battery, characterized in that: The secondary battery includes an electrode plate, which includes a current collector layer and an electrode film layer attached to the surface of the current collector layer; the current collector layer includes a current collector layer and an alloy layer stacked together, and the alloy layer is close to the electrode film layer; the electrode film layer includes an active material and a binder, and the content of the binder is 0 to 0.4 wt% based on the total mass of the electrode film layer.

2. The secondary battery according to claim 1, wherein: The electrode plate includes a negative electrode plate, and the tensile strength of the negative electrode plate is 400Mpa to 900Mpa; And / or, the electrode plate includes a positive electrode plate, and the tensile strength of the positive electrode plate is 200Mpa to 400Mpa.

3. The secondary battery according to claim 1 or 2, characterized in that: The surface roughness Ra of the alloy layer is 15nm-50nm.

4. The secondary battery according to any one of claims 1 to 3, characterized in that The electrode plate comprises a negative electrode plate, in which the adhesive force between the current collector layer and the electrode film layer is 12N / m to 25N / m; And / or, the electrode plate includes a positive electrode plate, and in the positive electrode plate, the adhesion between the current collector layer and the electrode film layer is 15N / m to 50N / m.

5. The secondary battery according to any one of claims 1 to 4, characterized in that The electrode plate includes a negative electrode plate, and the surface density of the negative electrode plate is 300 mg / cm 2 ~400mg / cm 2 ; And / or, the electrode plate includes a positive electrode plate, and the surface density of the positive electrode plate is 500 mg / cm 2 ~1000mg / cm 2 .

6. The secondary battery according to any one of claims 1 to 5, characterized in that The alloy layer contains at least four metal elements, including Co and Ni.

7. The secondary battery according to claim 6, characterized in that: The electrode plate includes a negative electrode plate, and in the negative electrode plate, based on the total mass of the alloy layer, the alloy layer includes: Fe: 23wt% to 40wt%, Co: 10wt% to 30wt%, Ni: 20wt% to 35wt%, Cu: 15wt% to 35wt%, and C: 7wt% to 15wt%; And / or, the electrode plate includes a positive electrode plate, in which, based on the total mass of the alloy layer, the alloy layer includes: Al: 17wt% ~ 29wt%, Fe: 16wt% ~ 29wt%, Co: 16wt% ~ 20wt%, Ni: 14wt% ~ 20wt%, Li: 15wt% ~ 21wt%.

8. The secondary battery according to any one of claims 1 to 7, wherein The thickness of the current collecting layer is 4 μm to 15 μm; And / or, the thickness of the alloy layer is 100nm to 500nm; And / or, the thickness of the electrode film layer is 25 μm to 100 μm.

9. The secondary battery according to any one of claims 1 to 8, wherein The electrode film layer also includes a conductive agent and a dispersant. Based on the total mass of the electrode film layer, the electrode film layer includes: 96wt% to 99wt% active material, 0.2wt% to 2.8wt% conductive agent, 0 to 1.5wt% dispersant, and 0 to 0.4wt% binder.

10. A method for preparing a secondary battery, characterized in that: include: Plasma spraying is used to form an electrode film layer on the surface of the current collector layer to obtain an electrode pole piece; wherein the current collector layer comprises a current collector layer and an alloy layer which are stacked, the alloy layer is close to the electrode film layer, the electrode film layer comprises an active material and a binder, and the content of the binder is 0 to 0.4 wt% based on the total mass of the electrode film layer; The electrode plate and the separator are combined to form a secondary battery.

11. The method for preparing a secondary battery according to claim 10, characterized in that: The electrode plate is a negative electrode plate, and the conditions of the plasma spraying include: The active material of the negative electrode plate includes a carbon material, and the temperature of the plasma spraying is 1000° C. to 3000° C.; and / or, The spraying rate of plasma spraying is 100 g / min to 200 g / min; and / or, Along the thickness direction of the electrode film layer, the distance between the plasma spraying nozzle and the surface of the electrode film layer is 100 mm to 250 mm; and / or, The spraying angle between the spraying direction of the plasma spraying and the thickness direction of the electrode film layer is 55° to 85°.

12. The method for preparing a secondary battery according to claim 10 or 11, characterized in that: The electrode plate is a positive electrode plate, and the conditions of the plasma spraying include: The temperature of plasma spraying is 800°C to 1500°C; and / or, The spraying rate of plasma spraying is 100 g / min to 200 g / min; and / or, Along the thickness direction of the electrode film layer, the distance between the plasma spraying nozzle and the surface of the electrode film layer is 100 mm to 250 mm; and / or, The spraying angle between the spraying direction of the plasma spraying and the thickness direction of the electrode film layer is 55° to 85°.

13. The method for preparing a secondary battery according to any one of claims 10 to 12, characterized in that: The alloy layer is formed on the surface of the current collecting layer by magnetron sputtering.

14. The method for preparing a secondary battery according to any one of claims 10 to 13, characterized in that: The alloy layer contains at least four metal elements, including Co and Ni.

15. The method for preparing a secondary battery according to claim 14, characterized in that: The electrode plate is a negative electrode plate. Based on the total mass of the alloy layer, the alloy layer includes: Fe: 23wt% to 40wt%, Co: 10wt% to 30wt%, Ni: 20wt% to 35wt%, Cu: 15wt% to 35wt%, and C: 7wt% to 15wt%; And / or, the electrode plate is a positive electrode plate, and based on the total mass of the alloy layer, the alloy layer includes: Al: 17wt% ~ 29wt%, Fe: 16wt% ~ 29wt%, Co: 16wt% ~ 20wt%, Ni: 14wt% ~ 20wt%, Li: 15wt% ~ 21wt%.

16. An electrical device, characterized in that: The invention comprises a secondary battery as claimed in any one of claims 1 to 9, or a secondary battery prepared by the method for preparing a secondary battery as claimed in any one of claims 10 to 15.

Citation Information

Patent Citations

  • Copper foil for secondary battery negative electrode power collector

    CN102725892A

  • Corrosion-resistant composite current collector and preparation method thereof

    CN118263447A

  • Positive plate and preparation method thereof, secondary battery and electric device

    CN118315596A

  • Dry-method composite electrode plate and lithium battery

    CN218274694U

  • Negative electrode for secondary battery and manufacturing method of the same and secondary battery using the same

    JP2004039407A